(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
For several decades now, the landscape has been studied from multiple fields due to its complexity and the wide variety of aspects it encompasses. Each discipline approaches the landscape from a particular perspective, analyzing both its physical characteristics and its cultural, social, and symbolic dimensions. Research has emphasized the reuse of the landscape, taking into account the living societies of the past and their evolution. The megalithic phenomenon follows the same diachronic line. For years, megalithism has been treated as a prehistoric element without understanding its reuse by different contemporary communities around it. The use of these elements has been prevalent throughout history, and it has been varied. Local communities have used these elements for purposes ranging from quarries for the extraction of raw materials to other types of functions. Therefore, it is necessary to understand megalithism as an evolutionary phenomenon connected to the changes of local communities. Thus, the reuse of the landscape and its resources along with subsequent societies, basing the study on the understanding of these elements that have come down to us as heritage to the present day. For this, the bidirectional socialization of megalithic heritage must be considered and studied in future research